SPEED, ACCURACY, AND FINANCIAL CONTROL: THE ROLE OF TECHNOLOGY IN FMCG DISTRIBUTION ACCOUNTING PRACTICES - Pande, Kiran Vasantrao; Kanetkar, Medha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Technology must be used to improve speed, accuracy, and financial control in the distribution of fast-moving consumer goods (FMCG) due to the growing complexity of financial management. The degree of technology use in FMCG distribution accounting and its effects on financial control are examined in this study. Using a structured questionnaire to gather primary data from 100 FMCG distributors in Nagpur, the study uses an F-test to examine the connection between financial control and technology use. According to the results, there is a notable improvement in financial management for companies that use digital accounting systems. However, obstacles including expense, inadequate infrastructure, and a lack of training prevent widespread implementation. The study comes to the conclusion that maximising accounting efficiency in FMCG distribution requires ongoing investment in digital tools and capacity-building programs.